A comparison of kicking accuracy for elite rugby players and a robotic kicker - Flemmer, C. L.; Flemmer, R. C (International Journal of Performance Analysis in Sport, 2015)
This work reports the average place kicking accuracy as a function of field position for players in the last two Rugby World Cup competitions and compares this accuracy with that of a robotic kicker.